World Bank Research Digest, Vol. 12(3) - World Bank (World Bank, Washington, DC, 2019)
This issue focuses on FCV Countries and Topics and features the following articles: Confronting the Development Challenges of Fragility, Conflict, and Violence; What Drives the Radicalization of Foreign Terrorist Recruits? The Cost of Fear; Leaving, Staying, or Coming Back? Migration Decisionsduring the Northern Mali Conflict; How Myanmar’s Reforms Are Playing Out in Rural Villages; Obstacles on the Road to Economic Growth in the West Bank; Can Public Works Help Postconflict Communities Escape Poverty? Can Mass Media Increase Women’s Political Participation after Civil War? Conflict and Poverty in Afghanistan’s Transition; Who Benefited from Burundi’s Demobilization Program? and U.S. Food Aid and Civil Conflict Revisited: A Methodological Caution .